Paraállami formák a mai magyar közigazgatásban - Balázs, István (Tér és Társadalom, 1999)
The concept of indirect administration contains all the administrational activities done by non-administrative authorities – established for this pursues in the given legal system. The authorisation can be a general law (e.g. in Hungary) or segmental in laws of certain sectors. The Hungarian legislation has adopted each directions of the local governmental charta (non-obligatory directions too) into the valid law of local governments, therefor regarding to legislation Hungary has one of the most liberate local governmental system in the world. Legal frames create unlimited possibility to the organisational implementation of indirect administration. Parastate administration models are present in Hungary in the necessary extent. However there are no need for their desultory and artificial spread because it doesn't strengthen the relationship of administration and civil sphere, but it takes the civil sphere under state control.